1994
DOI: 10.1080/00223980.1994.9921294
|View full text |Cite
|
Sign up to set email alerts
|

Are Age and Ethics Related?

Abstract: Ethical values of 171 college students at California State University, Chico, were measured, using a subset of the Rokeach (1968, 1971) Value Survey. Nonparametric statistical analysis, four value measures, and four different consistent tests of significance and probability showed, surprisingly, that the younger students were more ethical than the older students. College students under 21 scored significantly higher ethically on three out of the four measures. Younger college students valued equality, freedom,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
2
12
0
1
Order By: Relevance
“…75 38 Restoration options (patient may change their mind). 19 10 Endodontics and crowns although they are unlikely options. Overhanging margins with chronic periodontal involvement are discovered in an emergency patient whose usual dentist is on vacation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…75 38 Restoration options (patient may change their mind). 19 10 Endodontics and crowns although they are unlikely options. Overhanging margins with chronic periodontal involvement are discovered in an emergency patient whose usual dentist is on vacation.…”
Section: Resultsmentioning
confidence: 99%
“…With age comes a greater familiarity with professional norms and a reluctance to disrupt the status quo. 19,20 Even though the results of ethical tests may differ with age, the general direction of the results are similar for both young and old. 20 Ethical differences are rarely correlated with gender in studies of health professionals, 22,23 although males tend to express greater confidence in their ability to make sound ethical judgements.…”
Section: Sources Of Variations In Ethical Viewsmentioning
confidence: 90%
See 2 more Smart Citations
“…Age is a common segmentation criterion. Sikula and Costa (1994a) found, for instance, that younger students are more ethical than older ones (especially on the values equality, freedom, and honesty). Applied to fair trade, Baranzini (2005) found that the age bracket 35-45 is more disposed to buy ethically labeled products and is more informed about fair trade products.…”
Section: Segmentation Criteriamentioning
confidence: 96%